6 Questions for Socially Aware Language Technologies - Diyi Yang (Northern European Journal of Language Technology)
Over the last few decades, natural language processing (NLP) has dramatically improved performance and produced industrial applications like personal assistants. Despite being sufficient to enable these applications, current NLP systems largely ignore the social part of language. This severely limits the functionality and growth of these applications. This work discusses 6 questions towards how to build socially aware language technologies, with the hope of inspire more research into Social NLP and push our research field to the next level.